Investigation of rheological and particle characterisation techniques for the optimization of accelerated stability testing of sunscreen emulsion - Forbes, Patricia B.C. (University of Pretoria, 2025)
Dissertation (MSc (Chemistry))--University of Pretoria, 2024.